Abandoned Architectures in Santa Catarina: A window’s cartography - Nora, Lucas Rodrigo; Fiorin, Evandro (Revista Nacional de Gerenciamento de Cidades, 2022)
This article aims to identify characteristics of abandoned architecture in Santa Catarina territory through a cutout: the window. The window, as an object of study, is configured as the element that promotes the connection between the architectural space and the urban space, however, many windows of buildings in disuse no longer open and, many times, do not allow a great relationship between them. what is internal and what is external. Our observations were carried out in different parts of Santa Catarina using the Google Street View tool and the interpretations regarding the locations were described following the cartographic method of doing to know. Thus, maps and montages were organized that allow the visualization of intersections. In this sense, maps serve to promote a link between different territorialities that have common characteristics. This exercise allowed the visualization of singularities in each studied clipping. In this way, the results present some characteristics of the abandoned architectures in the state of Santa Catarina through approximations, but also, critical distance to pave the way for the deepening of research on the subject.